Global Citizenship and The Notion of Moral Emotions: Cognitive Polyphasia in Processes of Self-Other Constructions - Park, Eri; Sklad, Marcin (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
In the past, little attention has been paid to the socio-psychological dimension of the phenomenon of severe poverty in Africa. Despite the institutional nature of the global economic order, including policies of the European Union, the World Trade Organisation, and the International Monetary Fund, it is people who design, support, and maintain this system, and individual constructions of the world and structural inequalities reinforce one another. This also finds its expression in different ways in, e.g., peoples social representations of severe poverty in Europes former colonies (Park, 2008, 2011). This article investigates, how we members of the European middle class construct ourselves as ethical beings in the context of African poverty: What is the link between our social representations, identity construction and (in)action with regard to severe poverty in Africa? What are the discursive mechanisms we apply in the construction of an ethical self and what is the notion of the African Other? In a nutshell: What do our social represenations make us do